Exploring the genotypic potential of perilla (Perilla frutescens L.) for climate-resilient agriculture in the North Eastern Himalayas - Ansari, Meraj Alam; Kumar, Amit; Ahammed Shabeer, T. P.; Kumar, Alok; Roy, Subhra Saikat; Ansari, Majhrool Hak; Singh, Raghavendra; Sangeeta, Moirangthem; Layek, Jayanta; Prakash, Narendra; Mishra, Vinay K. (Frontiers in Sustainable Food Systems, 2025)
Perilla (Perilla frutescens (L.) Britton) is a potential but often neglected oilseed crop. It has a long cultivation history among tribal farmers in the hilly regions of North Eastern India and China. Perilla, with its rich fatty acids, essential nutrients, antioxidants, and phenolic acids, holds immense potential for climate-resilient agriculture in rainfed areas. Large-scale cultivation of perilla improves food security and offers numerous health benefits, including cardiovascular support and disease prevention, thereby enhancing human wellbeing. However, the genetic complexity of its fatty acid composition, nutrient content, and yield-associated agronomic traits remains poorly understood. To dissect the genetic basis, we evaluated 28 diverse genotypes of perilla across three growing seasons for eight agronomic traits and 16 biochemical traits, which revealed substantial phenotypic and biochemical variation. Agronomic traits displayed significant variability, with seed yield showing the highest coefficient of variation (CV), while leaf length showed the lowest CV. For oil quality traits, the maximum CV was observed for the omega-6:omega-3 ratio (12.08%) and the minimum for polyunsaturated fatty acids (PUFAs) (4.12%), with an average variation of 7.16%. Seed yield exhibited a positive correlation with copper (Cu), potassium (K), and iron (Fe), while PUFAs showed a positive correlation with omega-6 and a negative correlation with saturated fatty acids (SFAs). Principal component analysis indicated that the first two components explained 71.28% of the variance, with omega-6 and PUFAs: SFA contributing most to principal component 1 (PC1) and monounsaturated fatty acids (MUFAs) and omega-9 contributing most to principal component 2 (PC2). The genotypes RCT 30 and RCT 3 showed the highest contributions to both components (PC1 and PC2). This study provides valuable insights into the genotypic potential of perilla for enhancing its yield, oil quality, and nutrient composition, with significant implications for breeding programs aimed at developing climate-resilient varieties for the North Eastern Himalayas.